Diversity and Distribution Pattern of Woody Species in Bugarikallu Permanent Preservation Plot, Bannerghatta National Park, Bengaluru - Sharma, Balasubramanya; M., Manjunatha; P., Poorvashree; Saritha, Boya; Morab, Kiranraddi; C., Nagesh; Remadevi, O. K.; Dattaraja, H. S.; Suresh, H. S.; Vinaya Kumar, K. H.; Kakkar, Ritu (Indian Forester, 2023)
A one-hectare permanent forest vegetation plot was established in Bannerghatta National Park (BNP) to understand the influence of climate variability on dry forests of peninsular India. All woody individuals >1 cm dbh (diameter at breast height) were enumerated for species, given unique number, measured for size, and mapped for spatial location. The plot had 2165 individuals >1 cm dbh belonging to 76 species. Most abundant species was Ixora arborea, a shrub (333 individuals, 15.38% of abundance) followed by Anogeissus latifolia, a tree species (249 individuals, 11.50% of abundance). The top ten species accounted for 75.69% of the total abundance, 69.4% of individuals occurs in the 1-5 cm size class while 3 individuals >30 cm dbh occupy 10% of the total basal area. Tree species Anogeissus latifolia had the highest basal area in the plot; Anogeissus latifolia, Ixora arborea and Acacia chundra contribute to 42.4% of the total basal area of the plot. There were 35 angiosperm families with Fabaceae being the most speciose. There were 18 families with one species each. Decalepis hamiltonii, an endangered species occurred in the plot.